The visualization of power density and temperature distribution of electronic system using elliptic PDE solver - Alias, Norma; Satam, Noriza; A. Ghaffar, Zarith Safiza (Penerbit UTM Press, 2008)
The visualization of power density and temperature are critical in electronic-chip industries. Taking the advantages of mathematical algorithm that is based on elliptic equation of partial differential equation (PDE), the two-dimensional simulation has successfully been generated. The numerical iterative methods that are being used results in efficient elliptic PDE solvers. Numerical analysis is done in terms of execution time, number of iterations and computational complexity of the algorithm being used. The comparison is done between two iterative methods which are Gauss-Seidel and Red-Black Gauss Seidel. The elliptic solver is developed using C language and executed in Linux operating system's environment.